The Lecturers and Students’ Speech Act Used in Classroom Interaction: A Case Study - Andi Muhammad Syafri Idris; Gusnawaty Gusnawaty; Munira Hasjim; Kamsinah Kamsinah (HUMANIKA, 2023)
The speech act becomes a crucial major to provide the better conversation between people in the society or setting condition. The aim of the research is to explore the speech act used by the lecturer and students involving classroom interaction in teaching and learning process. In this research, the case study was used to examine the lecturer and students’ speech act in classroom interaction. The subject of the research was two lecturer and six students in linguistics program of faculty of cultural sciences, Hasanuddin University, Makassar in academic year 2022/2023. The sample was chosen by purposive sampling while the instrument of the research is observation and interview. In this research, the data will be analyzed by Searle’s Theoretical framework. The lecturer argues that the reason is using more directive speech acts is only to invite students to talk more and to carry out the principle of what Communicative Language Teaching is like believe. In this case, the directive is mostly dominant proposed by the lecturer in the teaching and learning process in the classroom interaction. It shows that the speech act used in the classroom can be powerful in the teaching and learning process for interaction in the classroom. The last, the implications can be seen from the finding that using directive speech acts that involve asking a lot of questions, asking, or governing contributes to student achievement, especially in productive skills.